Analisis Yuridis Eksploitasi Pada Remaja Sebagai Kurir Pengedar Narkotika - Salsabilla, Zalfa Uniqha; Dewi, Marsella Artika Sari; Asmarayani, Rahyuni Meylani; Aeni, Intan Nur; Rahman, Dia Ayu Yolanda (JATIJAJAR LAW REVIEW, 2025)
The involvement of adolescents in drug trafficking networks has become an alarming trend in Indonesia. Adolescents are frequently exploited as couriers by drug dealers due to the relatively lenient legal consequences they face under the juvenile justice system. This phenomenon arises from legal gaps within Law No. 11 of 2012 on the Juvenile Criminal Justice System and Law No. 35 of 2009 on Narcotics, which prioritize restorative justice approaches such as diversion. While these laws aim to protect children’s rights, in practice they are often misused by adult perpetrators to avoid harsher penalties by using minors as proxies. This study aims to analyze how these legal gaps are exploited and evaluate the challenges in enforcing narcotics law involving minors. A normative legal research method is used, focusing on statutory and conceptual approaches. The findings reveal that adolescents become involved as drug couriers due to social and psychological vulnerabilities such as peer pressure, lack of parental supervision, economic incentives, and low awareness of legal consequences.